Aminoferrocene-based prodrugs activated by reactive oxygen species - Hagen, Helen; Marzenell, Paul David; Jentzsch, Elmar; Wenz, Frederik; Veldwijk, Marlon Romano; Mokhir, Andriy (Disparate SAR data of Griseofulvin analogues for the dermatophytes trichophyton mentagrophytes, T. rubrum, and MDA-MB-231 cancer cells, 2011)
Cancer cells generally generate higher amounts of reactive oxygen species than normal cells. On the basis of this difference, prodrugs have been developed (e.g., hydroxyferrocifen), which remain inactive in normal cells, but become activated in cancer cells. In this work we describe novel aminoferrocene-based prodrugs, which, in contrast to hydroxyferrocifen, after activation form not only quinone methides (QMs), but also catalysts (iron or ferrocenium ions). The released products act in a concerted fashion. In particular, QMs alkylate glutathione, thereby inhibiting the antioxidative system of the cell, whereas the iron species induce catalytic generation of hydroxyl radicals. Since the catalysts are formed as products of the activation reaction, it proceeds autocatalytically. The most potent prodrug described here is toxic toward cancer cells (human promyelocytic leukemia (HL-60), IC50 = 9 μM, and human glioblastoma-astrocytoma (U373), IC50 = 25 μM), but not toxic (up to 100 μM) toward representative nonmalignant cells (fibroblasts).